Índices de produtividade e análise econômica de um sistema de produção de ovinos de corte no Semiárido. - Lira, Aianne Batista (2019)
The present research aimed to evaluate the reproductive efficiency, productive and economic indexes of Santa Inês and F1 Dorper ewes submitted to the reproduction model of a semiarid calving per year, as well as the growth characteristics of the lambs. A total of 93 ewes kept semi-extensively during two productive years from 2016 to 2017 were used. To evaluate the reproductive and productive efficiency of the ewes were calculated fertility, prolificacy, total birth weight (PTCN), weight total lambs weaned (PTCD), total weight of weaned lamb (PTCD) per farrowing lamb. For the growth characteristics of the lambs, birth weight (NW), weight at 28 days (P28), weight at weaning (PD) and average daily weight gain (GPMD), mortality of lambs were studied. Carcass characteristics were evaluated by average slaughter weight, hot and cold carcass weight and carcass yield as a function of weaning age and sex. The mathematical models used in the statistical analyzes included the fixed effects of the ewe and lamb genetic group, productive year, type of birth, sex of lambs, age of lambs, body condition score classes, age of ewe at calving and covariate coverage and all possible interactions. There was an effect (P <0.05) of the sheep score class on cover in relation to fertility and productive year. There was a significant effect (P <0.05) of productive years on PTCD, EROVD and fertility. From the genetic group of sheep in PTCD. From age to childbirth in proliferation, PTCN, PTCD, EROVP and EROVD. Significant effect (P <0.05) of body condition score (CE) at calving on herd reproductive efficiency, and EROVP. The age at weaning of lamb was significant (P <0.05) for GPMD. Year of birth influenced PD and GPMD. The genetic group influenced (P <0.05) all the analyzed variables. The sex of the offspring influenced (P <0.05) PN and P28 and the type of birth influenced (P <0.05) all variables. In the economic analysis, four scenarios were evaluated, the I being the real conditions, and the others had adjustments regarding the costs with food and the sale value of the product (meat), to a refrigerator or informal market. Scenario I presented the worst results, showing that sheep farming is not viable under the analyzed conditions. The best scenario was the IV, presenting the best economic indexes, where its costs were reduced and its sale value of the product was more valued. Given the data analyzed in all chapters, it can be seen that strategic management with climatic conditions improves the productive, reproductive and economic indexes of the production system. Reducing herd feed expenses is critical to good performance, as well as looking for technologies such as meat genetic groups, food flushing, creep feending, and looking for sales for commercial niches that pay the most for the product.